Pengembangan Model Pembelajaran Kooperatif Handep Berpasangan Berdasarkan Kaidah Quantum Teaching - Sarjoko, Sarjoko; Demitra, Demitra (Indonesian Journal of Curriculum and Educational Technology Studies, 2018)
This article describes the development of handep cooperative learning model consist of 3-4 members become pair handep cooperative learning model in the form of module and validated by experts and students who used it. The model of development used R2D2, that focused on the design and development stage. The draft of the model at the single-path prototype level validated by the learning expert and small group validation in context the of mathematics learning in secondary school, to get the model at alpha version level. The instrument is rubric and questionnaire for small group testing. The result of the research (1) the model has fulflled the principle of quantum teaching that is context orchestrations include an exciting learning atmosphere and solid foundation; (2) junior high school students rated the model interesting and fun; (3) learning steps that to be challenging on individual work steps and mutually assisting in solved the difcult problems for students individually; (4) the model has reached the alpha version level. Abstrak Artikel ini menjelaskan pengembangan model pembelajaran kooperatif handep beranggotakan 3-4 orang menjadi model kooperatif handep berpasangan dalam bentuk modul dan dinilai oleh pakar dan siswa yang menggunakannya. Model pengembangan yang digunakan adalah R2D2 (Recursive, Reï¬ective, Design and Development), difokuskan pada tahap design and development. Draf model pada level single path prototype divalidasi oleh pakar pembelajaran dan uji kelompok kecil dalam pembelajaran matematika di SMP, untuk mendapatkan model pada level alpha version. Instrumen berupa koesioner dengan pertanyaan terbuka untuk validasi ahli, dan angket respon siswa untuk uji kelompok kecil. Hasil penelitian (1) model telah memenuhi kaidah Quantum teaching yaitu orkestrasi konteks meliputi suasana belajar yang menggairahkan dan landasan yang kokoh, (2) siswa SMP menilai model tersebut menarik dan menyenangkan, (3) langkah-langkah pembelajaran yang dirasakan menantang pada langkah bekerja secara individual dan saling membantu secara bergiliran dalam memecahkan masalah sulit bagi siswa secara individual, dan (4) model telah mencapai level alpha version. Keywords: Aplha version; cooperative learning; pairs handep; quantum teaching; single path prototype